Covid-19 effects on tourism industry, case of Hungary - Alreahi, Mahmoud; Bujdosó, Zoltán (Acta Carolus Robertus, 2024)
Covid-19 had its critical effects on each aspect of life, especially on tourism sector. Both domestic and international tourism have suffered from the consequences to confront this pandemic, but the recovery and the adoption was not at the same level. This study aimed to give a closer view of both domestic and international tourism performance regarding covid-19 based on touristic accommodation facilities data of Hungary. The SPSS program was adopted to conduct the necessary statistical analysis, where the paired Student's t test was applied to analyse the data. The P-values of the test were significant for almost all of hypotheses. This study revealed that: (i) Covid had its bad effect on tourism, but it has changed tourists’ preferences; (ii) Domestic tourism had a better performance comparing with the international tourism except the revenue before and after covid era; and (iii) both, domestic and international tourism still need more time to recover and return to the previous situation.
Keywords: Covid; tourism; international; domestic; accommodation